Sequential therapy of portal vein embolization and systemic chemotherapy for locally advanced perihilar biliary tract cancer. Issue 1 (January 2023) - Takahashi, Atsushi; Yoshioka, Ryuji; Miyashita, Mamiko; Tanaka, Haruka; Oba, Masaru; Ichida, Hirofumi; Imamura, Hiroshi; Mise, Yoshihiro; Saiura, Akio
Abstract: Background: Curative resection is the only potential treatment for cure in patients with perihilar biliary tract cancer (PBTC). However, post hepatectomy liver failure (PHLF) due to insufficient future liver remnant volume (FRLV) remains a lingering risk even after portal vein embolization (PVE). This study aimed to investigate the feasibility and efficacy of a sequential treatment strategy consisting of PVE followed by preoperative chemotherapy before surgery. Methods: Between April 2019 and December 2021, 15 patients with locally advanced PBTC (LA-PBTC) underwent sequential treatment consisting of PVE followed by preoperative chemotherapy. The feasibility and efficacy, including resection rate, changes of FRLV, and chemotherapeutic effect, were investigated retrospectively. Results: Thirteen of 15 patients (86.6%) underwent curative resection. The median duration time between PVE and surgery was 144 days. FRLV/TLV ratio was 31.3% at prePVE, 38.4%, at two weeks after PVE, and 45.7% before surgery, respectively. There was significant increase in FRLV/TLV ratio two weeks after PVE. Additional increase in FRLV/TLV ratio was significantly achieved before surgery. PHLF occurred in 5 patients (38.4%). Pathological complete response was found in 2 of 13 patients (15.3%). Conclusions: Sequential PVE and systemic chemotherapy contribute to the sufficient hypertrophy of FRLV without compromising resectability in patients with LA-PBTC.